AKT1-Mediated NOTCH1 phosphorylation promotes gastric cancer progression via targeted regulation of IRS-1 transcription - Lingshan Zhou; Yuan Yang; Qian Qiao; Yingying Mi; Yuling Gan; Ya Zheng; Yuping Wang; Min Liu; Yongning Zhou (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose This study aimed to investigate that AKT1-Mediated NOTCH1 phosphorylation promotes gastric cancer (GC) progression via targeted regulation of IRS-1 transcription. Methods The study utilized databases such as PhosphositePlus, TRANSFAC, CHEA, GPS 5.0, and TCGA, along with experimental techniques including Western Blot, co-IP, in vitro kinase assay, construction of lentiviral overexpression and silencing vectors, immunoprecipitation, modified proteomics, immunofluorescence, ChIP-PCR, EdU assay, Transwell assay, and scratch assay to investigate the effects of AKT1-induced Notch1 phosphorylation on cell proliferation, invasion and migration in vitro, as well as growth and epithelial-mesenchymal transition (EMT) in vivo. Results AKT1 was found to induce phosphorylation of Notch1 at the S2183 site in GC, subsequently altering the subcellular localization of Notch1-IC and promoting its nuclear translocation. The transcription factor RBPJ that binds to Notch1 transcriptionally regulated IRS-1, CDH5, TNL1, ASCL2, and LRP6. Experimental validation revealed that Notch1-IC can regulate the expression of IRS-1. Overexpression of Notch1-IC was shown to promote the proliferation, invasion, and metastasis of GC cells, while knockdown of IRS-1 partially inhibited the aforementioned effects induced by Notch1-IC overexpression. Further experiments in vitro and vivo confirmed that AKT1-induced Notch1 phosphorylation can regulate the expression of IRS-1 and promote the malignant behavior of GC, including proliferation, invasion, metastasis, and EMT, with knockdown of IRS-1 partially reversing these effects. Conclusion AKT1 induces the Notch1 phosphorylation and promotes the activation and nuclear translocation of Notch1-IC by targeting the regulation of IRS-1, thereby advancing the progression of GC.